Earning Money from Laundry: Examining the Competitive Strategy of Contemporary Laundry Businesses in Increasing Revenue in Yogyakarta City - Wahyu Arief Putra; Siti Umi Khayatun Mardiyah (Return : Study of Management, Economic and Bussines, 2024)
The laundry business is very much found in every corner of Yogyakarta City. The number of these businesses encourages a variety of services offered to consumers. This study aims to explore and analyze the development strategy of the laundry service business in an effort to increase income. The main focus of this study is to identify the factors that drive business development, analyze the strategies implemented, and evaluate the effects of these strategies. In this qualitative study, the researcher interviewed eight laundry business owners in Yogyakarta City. This research shows that each business actor has different strategies in developing a business. The goals achieved by laundry business actors are service speed, service quality, and customer satisfaction. Laundry business actors diversify their businesses to increase customer satisfaction. This study concludes that the laundry business is a mainstream or ordinary business so the way to develop a business is with an optimal strategy. The more services offered, the more customers will come. The services offered by this business are of course by competing through price and quality. The profits obtained from this business are also quite promising with a large turnover every month.